Blood type evaluation in breast cancer patients at an oncology center in Agreste Pernambucano - de Oliveira Alves, Weverton; Marinho Batista Tavares Filho, Romero; Rios de Larrazábal, Bruna; Elaine Silva Germinio, Josefa; Lucia Peres de Medeiros, Adrya; Andrade Martins Esteves, Fabricio (O Mundo da Saúde, 2020)
Since the first report of an association between antigen A and the increased risk of stomach cancer, several studies have evaluated the involvement of the ABO blood group in cancer pathogenesis. Based on this hypothesis, this study aimed to identify blood typing as a risk factor for the development of breast cancer in a female population attended at the Oncology Center of Caruaru (CEOC) in Pernambuco. The ‘case’ group (n=50) was comprised of female patients diagnosed with breast cancer with a serologically confirmed ABO blood group. The ‘control’ group (n=50) was obtained from electronic medical records of patients without a diagnosis of cancer, with the same age. The frequency of distribution of blood groups was compared between cases (48% O, 40% A, 12% B, and 0% AB) and controls (44% O, 40% A, 14% B, and 2% AB). The findings of this study showed that there was no significant association between breast cancer and ABO blood group (p>0.05), in addition to the fact that no significant differences in clinical characteristics were observed between patients with different types of ABO blood.